1994
DOI: 10.1111/j.1741-4520.1994.tb00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Day‐12.5 and Day‐13.5 Fetal Mouse Palates Cultured in Vitro to 5‐Fluorouracil and Hydroxyurea

Abstract: The maxillary regions of day-12.5 and day-13.5 ICR mouse fetuses were cultivated in a chemically-defined serumless medium by a suspension culture technique to examine the toxic effects of 5-fluorouracil (5-FU) and hydroxyurea (HU) on cultured palates and to compare the sensitivity of fetal mouse palates at different stages of development. The palates of day-12.5 and day-13.5 fetal mice were explanted and exposed in vitro for 72 hr to 0.1-50 p g 5-FWml or to 5-76 p g HU/ml. 5-FU inhibited the growth and fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This fusion rate was similar to the figures obtained in our previous studies (Shiota et al 1990b;Kosazuma et al 1994;Mino et al 1994), suggesting that labeling palatal shelves with carbon particles did not significantly interfere with in vitro fusion of palatal shelves. Figure 1 shows three representative cases in which carbon marks were implanted at the anterior, middle, or posterior region of the palatal shelf of day-13 mouse fetuses.…”
Section: Resultssupporting
confidence: 78%
“…This fusion rate was similar to the figures obtained in our previous studies (Shiota et al 1990b;Kosazuma et al 1994;Mino et al 1994), suggesting that labeling palatal shelves with carbon particles did not significantly interfere with in vitro fusion of palatal shelves. Figure 1 shows three representative cases in which carbon marks were implanted at the anterior, middle, or posterior region of the palatal shelf of day-13 mouse fetuses.…”
Section: Resultssupporting
confidence: 78%
“…A list of references for those studies is provided for readers interested in this issue. Those references include: Bantle et al (1994), Bigot et al (1999), Bournias‐Vardiabasis (1990), Bremer et al (1999), Courchesne and Bantle (1985), Daston et al (1995), Dawson and Bantle (1987), Dawson and Wilke (1991), Dawson and Wilke (1992), Finch et al (1995), Guntakatta et al (1984), Kavlock et al (1987), Kemppainen et al (1996), Khera and Whalen (1988), Kosazuma et al (1994), Laschinski et al (1991), Lin (1987), Lynch et al (1991), Lyng (1989), Nito et al (1991), Sabourin et al (1985), Scholz et al (1999), Schuler et al (1985), Shiota et al (1990), Shirazi and Dawson (1991), Spielmann et al (1997), Steele et al (1988), Stringer and Blankemeyer (1995), Walmod et al (2004), and Wickramaratne (1987).…”
Section: 0 Developmental Toxicity Datamentioning
confidence: 99%
“…Day‐12.5 fetal mouse palates were explanted and cultivated for 72 h in a chemically defined medium supplemented with test compounds, and their toxic effects on cultured palates were evaluated by using some parameters for palatal growth and fusion. We used day‐12.5 fetal palates because cleft palate is most frequently produced in vivo when pregnant mice are treated with teratogens on day 12 of gestation (Shepard 1998; Schardein 2000) and because day‐12.5 fetal mouse palates are more susceptible to teratogenic chemicals than day‐13.5 palates (Kosazuma et al . 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In this culture system, explanted fetal secondary palates successfully closed within 72 h and the in vitro fusion of palatal shelves simulated the in vivo palatogenetic process both macroscopically and histologically. By using some chemical compounds, we have shown that the palate culture system is useful for assessing the teratogenicity of chemicals, especially their potential to cause cleft palate (Kosazuma & Kawauchi 1994; Kosazuma et al . 1994, 1995; Mino et al .…”
Section: Introductionmentioning
confidence: 99%